Eksploitasi Lingkungan dalam Cerpen Di Seine Meratapi Citarum melalui Pendekatan Ekokritik - Rizal Firmansyah; Turahmat Turahmat (Universitas Lampung, 2019)
Disasters, pollution, and animal hunting continue to occur unnoticed that humans are part of their lives. The purpose of this study is to explore the form of the study of the short story writer